Analisa Keberhasilan Implementasi Sistem Akuntansi Pemerintahan Berbasis Akrual pada Pemerintah Kabupaten Magelang - Widi Savitri Andriasari; Arief Prabowo (AkMen JURNAL ILMIAH, 2022)
This research was conducted to obtain an overview of the success of the Pemerintah Kabupaten Magelang in the application of accrual-based accounting. This study uses a qualitative approach method with a case study at the Dinas Pendapatan Pengelolaan Keuangan dan Aset Dearah by conducting interviews with officials and staff who are directly involved in the application of accrual-based accounting. Based on the results of the study, it shows that the successful implementation of the Accrual-Based Government Accounting System is influenced by the leadership’s commitment, regulations and policies, human resource management, and information technology management. The success of this implementation also has an impact on the quality of the Local Government Financial Report (LKPD) of Pemerintah Kabupaten Magelang which received Unqualified Opinions (Wajar Tanpa Pengecualian-WTP) from the Badan Pemeriksa Keuangan (BPK) for 4 consecutive years, namely in 2016, 2017, 2018 and 2019.